Rational Design of Spinel Oxide Nanocomposites with Tailored Electrochemical Oxygen Evolution and Reduction Reactions for ZincAir Batteries - Gnanaprakasam Janani; Yujin Chae; Subramani Surendran; Yelyn Sim; Woosung Park; Jung Kyu Kim; Uk Sim (Applied Sciences, 2020)
The unique physical and chemical properties of spinels have made them highly suitable electrocatalysts in oxygen evolution reaction and oxygen reduction reaction (OER & ORR). Zinc–air batteries (ZABs), which are safer and more cost-effective power sources than commercial lithium-ion batteries, hinge on ORR and OER. The slow kinetics of the air electrode reduce its high theoretical energy density and specific capacity, which limits its practical applications. Thus, tuning the performance of the electrocatalyst and cathode architecture is vital for improving the performance of ZABs, which calls for exploring spinel, a material that delivers improved performance. However, the structure–activity relationship of spinel is still unclear because there is a lack of extensive information about it. This study was performed to address the promising potential of spinel as the bifunctional electrocatalyst in ZABs based on an in-depth understanding of spinel structure and active sites at the atomic level.